PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS PERMAINAN CONGKLAK PADA MATERI ZAT ADITIF & ZAT ADIKTIF KELAS VIII DI SMP ISLAM TERPADU (IT) IBNU ABBAS TARAKAN - Rika Yulianti Ningsih; Fitri Wijarini; Fatmawati Fatmawati (Biopedagogia, 2021)
Abstract: The purpose of the research was to analyze the feasibility of congklak learning media on materials of additives of addictive substances for the eighth-graders at SMP Islam Terpadu (IT) Ibnu Abbas Tarakan based on material expert, media expert, and practitioners. The research design was Research and the Development (RD), which refers to the 4-D (four D) model developed by Thiagarajan et al. 1974. This model includes the stages of defining, designing, developing and disseminating. However, in this research, the researcher developed the learning media to the third stage D, the development stage. It was caused by the limitation of time and budget. The material expert validation analysis result was 80% in a feasible category. The media expert validation analysis result was 82% in a very feasible category. In addition, The result of the practitioners was 86% in a very feasible category. Based on the analysis results, it was concluded that the developed media had met the media eligibility standards. It was used as learning media. Keywords: : Learning Media, Congklak, Additives and Addictive Substances